2022
DOI: 10.2399/prn.22.0302009
|View full text |Cite
|
Sign up to set email alerts
|

Use of ureteral catheter in uterine-sparing surgery for placenta accreta

Abstract: Objective: The study aimed to investigate the effect of ureteral catheter use during surgery on the outcomes of obstetric and urinary complications in patients with placenta accreta spectrum (PAS) and placenta previa. Methods: The patients who were followed up at Meram Medical Faculty Hospital of Necmettin Erbakan University between January 2016 and November 2021 and diagnosed with PAS and placenta previa were included. Patients who underwent emergency and planned surgery were grouped as those with or without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…We consider that the low rate of urinary tract injury in our study was due to the low rate of bladder invasion cases. Recent studies indicated that preoperative utilization of ureteral catheters in PAS cases does not reduce the risk of urinary system injury [ 37 , 38 ]. Accordingly, we did not perform double-J catheter insertion before laparotomy to avoid ureteral injury in this study.…”
Section: Discussionmentioning
confidence: 99%
“…We consider that the low rate of urinary tract injury in our study was due to the low rate of bladder invasion cases. Recent studies indicated that preoperative utilization of ureteral catheters in PAS cases does not reduce the risk of urinary system injury [ 37 , 38 ]. Accordingly, we did not perform double-J catheter insertion before laparotomy to avoid ureteral injury in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Uterine-sparing surgery is performed by a multidisciplinary team in our clinic, and cesarean hysterectomy is performed in cases in which bleeding cannot be controlled as previously described for PAS [ 16 ]. After a preoperative evaluation by the urology team, we inserted a cystoscope-guided bilateral ureteral catheter in cases of suspected bladder or parametrium invasion (this not possible in some very urgent cases).…”
Section: Methodsmentioning
confidence: 99%